The Effect of Adoption Thai Financial Reporting Standard 15 Revenue from Contract with Customers on Earnings Quality of Companies in the Property and Construction Sectors in Stock Exchange of Thailand - Krassanairawiwong, Krassanee; Srijunpetch, Sillapaporn (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2020)
The objective of this research is to investigate the relationship between the change in revenue and earnings quality. The study of earnings quality is conducted by analyzing management discretion in accruals based on The Modified Jones model (Dechow, Sloan & Sweeney, 1995) and Yoon, Miller and Jiraporn (2006) model and comparing those discretionary accruals between pre-adoption and post-adoption of TFRS 15 Revenue from Contracts with Customers which was firstly implemented in Thailand in B.E. 2562. The data is collected from samples of company in the property and construction development industry in the Stock Exchange of Thailand. The Collected data was analyzed by using descriptive statistics and inferential statistics methods. The results reveal that according to The Modified Jones Model, the change in revenue is correlated with the earnings quality through discretionary accruals, whereas Yoon Model shows no essential correlation between the change in revenue and earnings quality through discretionary accruals. In addition, there is no difference when comparing discretionary accruals based on The Modified Jones Model and Yoon Model between the pre-adoption and post-adoption of Thai Financial Reporting Standard (TFRS) 15.